The rock slope failures at Låvan and Dusnjarga, Northern Norway. A comprehensive Quaternary, morphological and structural analysis - Blau, Frederic (UiT Norges arktiske universitet, 2020)
Rock avalanches and subsequent displacement waves represented the deadliest natural disaster in Norway in the past century. The two deep-seated and unstable slopes Dusnjarga and Låvan in Troms county (Norway) are clearly defined by morphological deformation features. Due to the steep fjord setting, a potential catastrophic rock avalanche could pose a severe threat to people and infrastructure along the fjord and in particular for the settlement below Låvan. Firstly, an analysis of Quaternary deposits and landforms in the study area was performed which involved e.g. the creation of a detailed Quaternary geological map, the sedimentary logs and particle size analyzes. The former glaciation and deglaciation were expressed by thin till layers, glaciomarine and redeposited glaciofluvial deposits as well as paleo-shorelines. Their analysis and interaction with the rock slope deformation allowed for several interpretations on the temporal behavior of the instabilities. For instance, for Dusnjarga’s central and eastern parts, strong deformation is suggested for the approximate period of the Tapes transgression. Due to the general scarcity of Quaternary deposits in the study area further reaching chronological interpretations would however require the use of absolute dating methods. Secondly, the rock slope deformation Låvan was investigated in detail using digital resources as well as data from the field which comprised structural measurements, scanline data and observations on the morphology and rock mass. Four discontinuity sets were clearly expressed in both the structural data and the morpho-structures: the foliation (SC) and the joint sets JN1, JN2 and JN3. Kinematically, planar failure on SC and wedge failure on JN1 and SC stood out as the most likely failure mechanisms. Bilinear compound sliding on multiple sliding surfaces was suggested as the controlling style of deformation. Sliding occurs as suggested principally on SC with the steeply dipping JN2 forming the linkage between low-persistent fractures. A change ...